School variables and senior secondary students achievement in mathematics in Rivers State, Nigeria - Daso, P.O. (2013)
This research study focused on the relationship between school variables and students' achievement in mathematics at the senior secondary II level in Rivers State, Nigeria. The ex-post-factor research design was adopted for this study since already conducted mathematics test scores of the students were retrieved and used for the analysis. Furthermore, data were elicited through the school variables and students achievement in mathematics questionnaire (SVASAMQ). A population of 10,373 comprising of senior secondary II students and principals were involved in the study; out of which 4661 were chosen for the sample using the Yarrow Yamen's formula. The data were analyzed using the Z-test statistic, means and simple percentages. The findings were that there is a significant relationship between teacher quality, school academic climate and students' achievement in mathematics. Hence some recommendations were made.
KerkoCite.ItemAlsoKnownAs: 10.5901/mjss.2013.v4n2p709 4893635:RDZZE5RP 5168324:94XH5VEU
Keywords: Learning outcomes; Mathematics education; Secondary education; Teacher knowledge and skills; _C:Nigeria; _authorsString:Second; A.B.; _checkedWith:AERD; _research:Quantitative; _type:Peer-reviewed article; ⚠️ Invalid DOI